2015
DOI: 10.4149/neo_2015_090
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes in ulcerative colitis associated colorectal cancer based on centrality analysis of co-expression network

Abstract: PreviousColorectal cancer (CRC) is a well-recognized complication of Ulcerative colitis (UC) and patients with UC have a higher incidence of CRC than the general population. Early detection and mechanism of colitis-associated colorectal cancer (CAC) is still challenging. The aim of present study is to identify genes associated with CAC by centrality analysis of co-expression networks. Co-expression networks of CRC and UC were constructed by empirical Bayes approach based on top 200 gene signatures which identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For CRA, a study by Mclean et al showed that the inflammatory cytokine genes CXCL1, CXCL2, CXCL3, CCL20, IL8 (CXCL8), CCL23, CCL19, CCL21, and CCL5are BioMed Research International 4) and CEACAM7 (carcinoembryonic antigen-related cell adhesion molecule 7) have been found to be associated with an unfavourable prognosis in CRC [41]. SLC4A4 was also found to be a differentially expressed gene common to UC and CRC [42]. The downregulation of CEACAM7 expression in hyperplastic polyps and early adenomas represents some of the earliest observable molecular events leading to CRC [43].…”
Section: Discussionmentioning
confidence: 99%
“…For CRA, a study by Mclean et al showed that the inflammatory cytokine genes CXCL1, CXCL2, CXCL3, CCL20, IL8 (CXCL8), CCL23, CCL19, CCL21, and CCL5are BioMed Research International 4) and CEACAM7 (carcinoembryonic antigen-related cell adhesion molecule 7) have been found to be associated with an unfavourable prognosis in CRC [41]. SLC4A4 was also found to be a differentially expressed gene common to UC and CRC [42]. The downregulation of CEACAM7 expression in hyperplastic polyps and early adenomas represents some of the earliest observable molecular events leading to CRC [43].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, some researchers hold that hub analysis of the coexpression network could overcome this limitation to some degree ( 42 , 43 ). Closeness is one of the most important metrics for finding hubs in a network ( 27 , 44 ). Closeness is the length of the shortest path from one node to another.…”
Section: Discussionmentioning
confidence: 99%
“…Closeness centrality of a certain node is the combined shortest distance from all other nodes. Closeness centrality represents the potent influence of a node on the network ( 27 ). The closeness scores of nodes in the coexpression network were calculated using the CytoHubba plug-in ( 28 ) in Cytoscape.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, primary tumors and their paired metastases frequently revealed many genes to be altered in common at both sites; these findings support the existence of a very close genomic relationship between the GEP of primary colorectal tumors and their paired liver metastases, as it has also been suggested to occur at the DNA level [16]. Deregulated expression observed in common in both groups of (paired) tumor samples included increased expression of genes linked to liver metastatic sCRC, tumor development, growth (TACSTD2) [17] and invasiveness (FOXQ1, MMP7 and CLDN1) [18, 19], together with decreased expression of genes related to differentiation (CLCA4, CLCA1 and AQP8) [20, 21], apoptosis (CA1) [22], immunity (ZG16) [23], and protection (FCGBP and CA2) [24] of CRC cells. Thus, the functional networks most strongly affected in primary tumors included those involved in focal adhesion, PI3K-Akt and ErbB signaling and other cancer pathways, FcδR-mediated phagocytosis, endocytosis, bacterial invasion of epithelial cells, plus the TP53 signaling pathway, all of which have been previously shown to be directly involved in the development and progression of sCRC [25–29].…”
Section: Discussionmentioning
confidence: 99%